Fibroblasts in urothelial bladder cancer define stroma phenotypes that are associated with clinical outcome - Mezheyeuski, Artur; Segersten, Ulrika; Leiss, Lina Wik; Malmström, Per-Uno; Hatina, Jiri; Östman, Arne; Strell, Carina (Scientific reports, 2020)
Little attention was given to the interaction between tumor and stromal cells in urothelial bladder carcinoma (UBC). While recent studies point towards the existence of different fibroblast subsets, no comprehensive analyses linking different fibroblast markers to UBC patient survival have been performed so far. Through immunohistochemical analysis of five selected fibroblast markers, namely alpha smooth muscle actin (ASMA), CD90/Thy-1, fibroblast activation protein (FAP), platelet derived growth factor receptor-alpha and -beta (PDGFRa,-b), this study investigates their association with survival and histopathological characteristics in a cohort of 344 UBC patients, involving both, muscle-invasive and non-muscle-invasive cases. The data indicates that combinations of stromal markers are more suited to identify prognostic patient subgroups than single marker analysis. Refined stroma-marker-based patient stratification was achieved through cluster analysis and identified a FAP-dominant patient cluster as independent marker for shorter 5-year-survival (HR(95% CI)2.25(1.08-4.67), p = 0.030). Analyses of interactions between fibroblast and CD8a-status identified a potential minority of cases with CD90-defined stroma and high CD8a infiltration showing a good prognosis of more than 80% 5-year-survival. Presented analyses point towards the existence of different stroma-cell subgroups with distinct tumor-modulatory properties and motivate further studies aiming to better understand the molecular tumor-stroma crosstalk in UBC.
Keywords: Cluster Analysis; Receptor, Platelet-Derived Growth Factor alpha; fenotyp; Aged; serinové endopeptidasy; Membrane Proteins; CD8-pozitivní T-lymfocyty; senioři; Thy-1 Antigens; prognóza; Biomarkers, Tumor; CD8-Positive T-Lymphocytes; nádory močového měchýře; lidé; aktiny; fibroblasty; endopeptidasy; Prognosis; shluková analýza; proporcionální rizikové modely; Kaplan-Meier Estimate; nádorové biomarkery; Proportional Hazards Models; Female; želatinasy; Male; antigeny Thy-1; ženské pohlaví; Fibroblasts; Humans; růstový faktor odvozený z trombocytů - receptor alfa; mužské pohlaví; Kaplanův-Meierův odhad; Endopeptidases; Actins; Serine Endopeptidases; Urinary Bladder Neoplasms; membránové proteiny; Phenotype; Gelatinases